El trasfondo metafísico de las cinco vías de Santo Tomás: Una aproximación desde Lawrence Dewan, O.P. (2011)
Lawrence Dewan presents an approach of St. Thomas s Five Ways to God which surpasses in metaphysical fineness and intellectual deepness the numerous excellent presentations about this topic. Dewan; in presenting the Metaphysical framework which serves as an argumentative foundation of the Five Ways; demonstrates; once again; to be an expert knower of Saint Thomas Aquinas s work. Likewise; the different writings which Dewan has dedicated to this subject allow him to use nuclear notions of Thomism that master Dewan has rethought and; so to speak; refreshed with quite unusual scientific rigor. Such notions are; for example: the central role of the substantial form and the vision of esse as a nature.